2014
DOI: 10.1515/jbcpp-2013-0162
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of serum γ-glutamyltransferase and uric acid on metabolic, hepatic and kidney parameters in subjects at high altitudes

Abstract: At high altitude, increased γGT levels were associated with hyperglycemia; increased uric acid levels were associated with overweight/obesity, hemoglobin, dyslipidemia, high blood pressure and kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…GGT is a cell surface enzyme that hydrolyzes the γ-glutamyl bond of extracellular reduced and oxidized GSH into glutamate, cysteine (Cys), and glycine (Gly) ( 62 ). In line with the heightened GGT level at high altitudes ( 35 ), we found that GGT levels were much higher in Tibetans than in Hans. Moreover, higher GGT levels were reported in the group with impaired fasting glucose than in those with normal fasting glucose in the Chinese population ( 63 ), and GGT level was increased to a greater extent by high UA in Hans than in Tibetans ( Figure 3I ), indicating increased cleavage of GSH in Hans other than Tibetans.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…GGT is a cell surface enzyme that hydrolyzes the γ-glutamyl bond of extracellular reduced and oxidized GSH into glutamate, cysteine (Cys), and glycine (Gly) ( 62 ). In line with the heightened GGT level at high altitudes ( 35 ), we found that GGT levels were much higher in Tibetans than in Hans. Moreover, higher GGT levels were reported in the group with impaired fasting glucose than in those with normal fasting glucose in the Chinese population ( 63 ), and GGT level was increased to a greater extent by high UA in Hans than in Tibetans ( Figure 3I ), indicating increased cleavage of GSH in Hans other than Tibetans.…”
Section: Discussionsupporting
confidence: 79%
“…When we compared the incidence of hyperuricemia between native Tibetans and immigrant Hans at the three altitudes in the Tibetan region, we found a similarly high prevalence of hyperuricemia between the two ethnicities but with distinct biochemical mechanisms. Hyperuricemia is closely associated with obesity and metabolic disturbances such as insulin resistance, dyslipidemia, hypertension, and kidney disease in lowlanders ( 34 ) and highlanders in Tibet ( 1 ) and Peru ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal adaptation response to high altitude can cause physio-pathological changes of varying organs and tissues. Specifically, it was reported that high altitude could induce irreversible/reversible damage to high oxygen and energy demanding tissues, such as the brain, heart, liver, gastrointestinal tract, and ocular tissue, over a certain period of time (15)(16)(17)(18)(19)(20). The clinical characteristics commonly include blood pressure fluctuation, loss of memory function (declined cognitive function), absence of equilibrium function, headache, indigestion, decreased appetite, and so on (21)(22)(23)(24).…”
Section: High-altitude Heart Diseasesmentioning
confidence: 99%